2013
DOI: 10.7287/peerj.preprints.78v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient algorithms for sampling feasible sets of macroecological patterns

Abstract: Ecological variables such as species richness (S) and total abundance (N) can strongly influence the forms of macroecological patterns. For example, the majority of variation in the species abundance distribution (SAD) can often be explained by the majority of possible forms having the same N and S, i.e. the feasible set. The feasible set reveals how variables such as N and S determine observable variation and whether empirical patterns are exceptional to the majority of possible forms. However, this approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We constructed the feasible set of partitions and the feasible set of compositions for each pair of (Qi, Ni) in the empirical relationship. Given the large size of the feasible set for large values of (Qi, Ni) (Locey and White 2013), we drew 1000 random configurations from the feasible set for each (Qi, Ni) using the algorithms from Locey and McGlinn (2013). We confirmed that 1000 samples were sufficient in this context by testing sample sizes of 4000, which yielded equivalent results (Appendix B, Fig.…”
Section: Analysesmentioning
confidence: 76%
“…We constructed the feasible set of partitions and the feasible set of compositions for each pair of (Qi, Ni) in the empirical relationship. Given the large size of the feasible set for large values of (Qi, Ni) (Locey and White 2013), we drew 1000 random configurations from the feasible set for each (Qi, Ni) using the algorithms from Locey and McGlinn (2013). We confirmed that 1000 samples were sufficient in this context by testing sample sizes of 4000, which yielded equivalent results (Appendix B, Fig.…”
Section: Analysesmentioning
confidence: 76%
“…To choose appropriate patterns of dominance for the species in our dominant communities, we simulated species abundance distributions (SADs) using an algorithm that generates random partitions (i.e., abundance values for each species), constrained by the total sum of individuals (30 for pollinators and 140 for plants) and species richness (five for pollinators and seven for plants; Fig. a, b) using the rpartitions package (Locey and McGlinn ). We then retained a subset of simulated communities that had a SAD dominance skew in the 99th percentile of all simulated communities (i.e., the most dominant communities), and calculated average abundance values for each species in this subset.…”
Section: Methodsmentioning
confidence: 99%
“…A lower value of AIC (DAIC) indicates a better model. [46]. Scripts are available in the electronic supplementary material.…”
Section: (C) Analysis Of Aggregationmentioning
confidence: 99%
“…One random configuration corresponds to a potential distribution of P parasites among H hosts. This random partitioning is repeated many times, and the sampled configurations are an estimate of the feasible set given P and H [22,46]. The feasible set approach makes no mechanistic assumptions but predicts the most likely aggregation level given data constraints (see electronic supplementary material), effectively recognizing that many combinations of mechanisms can generate similar levels of aggregation [25,47].…”
Section: (C) Analysis Of Aggregationmentioning
confidence: 99%
See 1 more Smart Citation